Immunomodulatory Effects and Mechanisms of Two-Dimensional Black Phosphorus on Macrophage Polarization and Bone Regeneration - Zou Y; Xie Q; Lin J; Dong H; Zhuang X; Xian R; Liang Y; Li S (International Journal of Nanomedicine)
Yue Zou,1,* Qinkai Xie,1,* Jiating Lin,1 Hao Dong,1 Xianxian Zhuang,1 Ruoting Xian,1 Youde Liang,2,3 Shaobing Li1 1Center of Oral Implantology, Stomatological Hospital, School of Stomatology, Southern Medical University, Guangzhou, People’s Republic of China; 2Department of stomatology center, The People’s Hospital of Baoan Shenzhen, Shenzhen, People’s Republic of China; 3The Second Affiliated Hospital of Shenzhen University, Shenzhen, People’s Republic of China*These authors contributed equally to this workCorrespondence: Youde Liang, Department of stomatology center, The People’ s Hospital of Baoan Shenzhen, No. 118 Longjing 2nd Road, Xin’an Street, Bao’an District, Shenzhen, 518100, People’s Republic of China, Email liangyoude1229@sina.com Shaobing Li, Center of Oral Implantology, Stomatological Hospital, School of Stomatology, Southern Medical University, No. 366, South of Jiangnan Boulevard, Guangzhou, 510280, People’s Republic of China, Email issaclee@163.comAbstract: The repair of bone defects poses a significant challenge within the realm of clinical medicine. However, with the advent of various emerging biotechnologies, bone tissue engineering (BTE) has emerged as a promising discipline that offers innovative therapeutic strategies to address bone defects. Among the novel biomaterials being explored, two-dimensional (2D) black phosphorus (BP) has attracted considerable attention due to its advantageous properties, which include antimicrobial activity, drug delivery capabilities, and effective photothermal conversion. These properties render BP an excellent candidate for BTE applications. Recent studies have indicated that BP possesses remarkable immunomodulatory properties that influence bone regeneration, profoundly impacting the transformation of the osteoimmune microenvironment, thereby guiding the process of bone remodeling. Macrophage is a principal component of the osteoimmune microenvironment, and evidence suggests that BP significantly influences the polarization of macrophage M1 and M2 phenotypes. This review aims to present the regulatory effects and underlying mechanisms of 2D BP on macrophage polarization in the immune microenvironment. It highlights the ability of BP to systematically modulate the inflammatory environment and to facilitate the metabolic reprogramming of macrophages. The review concludes with a discussion of the potential applications and limitations of BP nanomaterials in the field of BTE.Keywords: osteoimmune microenvironment, macrophage metabolic reprogramming, cell interaction, bone remodeling